Intercoronary Continuity with Bidirectional Flow: Dynamic Changes Parallel to Coronary Disease Progression - Weinstein, JM; Ilia, R (Journal of Hypertension and Cardiology, 2014)
Direct intercoronary continuity is a rare angiographic finding. We report an unusual case of a 51-year old male with coronary disease who demonstrated intermittent variability in the directions of flow as a result of changes in his coronary disease.
Keywords: Angiography; intercoronary continuity; flow directions